Effect of Methyl Tertiary Butyl Ether (MTBE) Blending in Pertalite Fuel on Engine Performance and Exhaust Emissions of a 125 cc Vario Motorcycle - Musthofa, Imron; Muhajir, Muhamad; Putra, Muhammad Rezki Fitri; Adhielia Noer Syaief, Adhielia Noer; Isworo, Hajar; Ivana, Reza Taufiqi (Penerbitan Universitas Trisakti, 2026)
The use of Methyl Tertiary Butyl Ether (MTBE) as an additive in Pertalite fuel has gained attention due to its potential to improve engine performance and reduce exhaust emissions in motorcycles. This study aims to evaluate the effects of MTBE on engine torque, power, and exhaust emissions in a Honda Vario 125cc using three fuel mixtures: standard Pertalite, Pertalite with 10% MTBE, and Pertalite with 20% MTBE. The experimental methodology involved measuring engine performance using a dynotest and analyzing emissions using an exhaust gas analyzer. Fuel consumption was also recorded to assess efficiency. The results revealed that the 10% MTBE mixture (A10) significantly increased engine torque and power compared to the standard Pertalite, while reducing CO emissions. However, the 20% MTBE mixture (A20) led to reduced performance and increased emissions, particularly hydrocarbons, indicating that excessive MTBE negatively impacts combustion efficiency. The optimal concentration of MTBE was found to be 10%, which balanced performance improvement with emission reduction. These findings highlight the potential of MTBE to optimize fuel performance and reduce environmental impact. Future research should explore other fuel additives and further refine MTBE concentrations for more sustainable fuel formulations.